Sweetened Packaged Beverage Purchase Intention and Behavior based on Subjective Norm, Perceived Risk, and Perceived Value - Khofanda, M; Fajarindra Belgiawan, P (KnE Social Sciences, 2018)
In the recent decade, sweetened packaged beverages have risen in Indonesia. Several studies have verified its adverse effects on health, and Indonesian media publish it frequently on their portals. It is necessary to investigate the relationship between the product purchase intention and frequency, with people’s perceived risk on the product and their exposure from media - including about the products’ adverse effects. This research surveyed 254 respondents via online questionnaire quantitatively. Then, principal component analysis is conducted to construct the perceived risk, perceived value, and subjective norm. Afterward, ordinal logistic regression is deployed to measure whether there is a significant relationship between those mentioned factors toward purchase intention. Finally, we conducted ordinary least square to test the significant relationship between intention and actual purchase behavior/frequency. It is found that only perceived value on the product and respondents’ reference group opinion on consuming the product significantly affects their purchase intention and actual purchase behavior. This means, neither perceived risk on the product nor media exposure affects respondents’ purchase intention and behavior. These findings are encouraging for sweetened packaged beverages company, while health officials and activists may find these results unfavorable. Keywords: sweetened packaged beverages; theory of planned behavior; purchase intention; perceived risk; perceived value; mass media